Solve for g 7+(5g)/2=-13

Math
7+5g2=-13
Move all terms not containing g to the right side of the equation.
Tap for more steps…
Subtract 7 from both sides of the equation.
5g2=-13-7
Subtract 7 from -13.
5g2=-20
5g2=-20
Multiply both sides of the equation by 25.
25⋅5g2=25⋅-20
Simplify both sides of the equation.
Tap for more steps…
Simplify 25⋅5g2.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
25⋅5g2=25⋅-20
Rewrite the expression.
15⋅(5g)=25⋅-20
15⋅(5g)=25⋅-20
Cancel the common factor of 5.
Tap for more steps…
Factor 5 out of 5g.
15⋅(5(g))=25⋅-20
Cancel the common factor.
15⋅(5g)=25⋅-20
Rewrite the expression.
g=25⋅-20
g=25⋅-20
g=25⋅-20
Simplify 25⋅-20.
Tap for more steps…
Cancel the common factor of 5.
Tap for more steps…
Factor 5 out of -20.
g=25⋅(5(-4))
Cancel the common factor.
g=25⋅(5⋅-4)
Rewrite the expression.
g=2⋅-4
g=2⋅-4
Multiply 2 by -4.
g=-8
g=-8
g=-8
Solve for g 7+(5g)/2=-13

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top